Facile low-temperature polyol process for LiFePO4 nanoplate and carbon nanotube composite - Wu, G.; Zhou, Y.; Gao, X.; Shao, Zongping (Elsevier, 2013)
Crystalline LiFePO4 nanoplates were incorporated with 5 wt.% multi-walled carbon nanotubes (CNTs) via a facile low temperature polyol process, in one single step without any post heat treatment. The CNTs were embedded into the LiFePO4 particles to form a network to enhance the electrochemical performance of LiFePO4 electrode for lithium-ion battery applications. The structural and morphological characters of the LiFePO4-CNT composites were investigated by X-ray diffraction, Fourier Transform infrared spectroscopy, Raman spectroscopy, scanning electron microscopy and transmission electron microscopy. The electrochemical properties were analyzed by cyclic voltammetry, electrochemical impedance spectroscopy and charge/discharge tests. Primary results showed that well crystallized olivine-type structure without any impurity phases was developed, and the LiFePO4-CNT composites exhibited good electrochemical performance, with a reversible specific capacity of 155 mAh g-1 at the current rate of 10 mA g-1, and a capacity retention ratio close to 100% after 100 cycles.